Stability Results of Additive-Quadratic \(n\)-Dimensional Functional Equation: Fixed Point Approach - Karthikeyan, S.; Rassias, J. M.; Vijayakumar, S.; Sakthivel, K. (Communications in Mathematics and Applications, 2022)
In this paper, the authors discussed the Ulam-Hyers stability results of \(n\)-dimensional mixed type additive and quadratic functional equation: align* ^n_i=1f\!(^n_j=1x_ij)\!& = (-n^2+7n-62)\!\! _i=1^n f(x_i)+\!(-n^2+5n-22)\!\! _i=1^n f(-x_i) &+(n-42) _1i<jn(f(x_i+x_j) +f(-x_i-x_j)) align* where align* x_ij= cases -x_j&if i=j, x_j &if i eq j, cases align* in Banach spaces using fixed point method.